Global burden of esophageal cancer attributable to smoking: a systematic analysis for the Global Burden of Disease Study 2019 - Wu, Shilong; Jiang, Wenfa; Li, Jiufei; Wu, Zeqin; Xu, Chenyang; Xie, Ning (Frontiers in Oncology, 2023)
Background Epidemiological trends of esophageal cancer attributable to smoking remain unclear. This study aimed to estimate the spatiotemporal trends of the esophageal cancer burden attributable to smoking to assist in global esophageal cancer prevention and smoking cessation. Methods Data on esophageal cancer attributable to smoking were obtained from the Global Burden of Disease Study 2019. The number and age-standardized rates of esophageal cancer mortality (ASMR) and disability-adjusted life years (ASDR) were analyzed by age, sex, and location. Joinpoint regression analysis was used to analyze the temporal trends of esophageal cancer burden attributable to smoking over 30 years. Results In 2019, the number of global esophageal cancer deaths and disability-adjusted life years (DALYs) attributable to smoking was approximately 203,000 and 475 million, respectively. The global esophageal cancer deaths and DALYs due to smoking were approximately 1.5-fold increased from 1990 to 2019, but the corresponding ASMR and ASDR had decreased. The heaviest burden occurred in East Asia, Mongolia, and the middle socio-demographic index (SDI) region. The male-to-female ratio was approximately 12.7 in the esophageal cancer deaths and DALYs and was approximately 14.3 in the ASMR and ASDR. The heaviest burden appeared in the 60–74 years age group. The estimated annual percentage change (EAPC) in ASMR was highly negatively associated with ASMR in 1990 (ρ = −0.41, p < 0.001) and SDI in 2019 (ρ = −0.29, p < 0.001). Conclusion Despite reductions in ASMR and ASDR, the esophageal cancer burden attributable to smoking remains heavy, especially in middle SDI regions. Active tobacco control can reduce esophageal cancer burden.